Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi - Wicaksari, Yulana; Wulandari, Sartika (Jurusan Akuntansi Politeknik Negeri Padang, 2021)
Purpose of this study was to determine the effect of taxpayer awareness, quality of tax services, tax sanctions, tax knowledge0and tax amnesty on individual taxpayer compliance. Sample in this study were 100 individual taxpayers at the Tax Service Office (KPP) in the city of Semarang. Data used in this study is primary data by distributing questionnaires to0respondents using google form. Sample selection in this study used accidental sampling using the Slovin formula. After fulfilling0the classical assumption test, then the data were analyzed using multiple linear regression analysis techniques. Results showed that taxpayer awareness, tax sanctions, tax knowledge and tax amnesty had a positive effect on individual taxpayer compliance. While the quality of tax services does not affect the compliance of individual taxpayers. Value of the coefficient0of determination test with the individual taxpayer compliance value of 41.90 percent can be explained by the research variables. The result of this study can be input for the government what should be done to improve taxpayer compliance.